Alkaline gelatinized locust bean gum: Alternative depressant for pyroxene and talc in Platreef ore - Walter Amos Ngobeni; Antoine F. Mulaba-Bafubiandi (South African Journal of Chemical Engineering, 2025)
Carboxymethyl cellulose (CMC) is a common depressant used in flotation. However, CMC has a high negative charge density. This results in stronger electrostatic repulsion on negatively charged minerals. Also, it is susceptible to pulp ionic strength. Hence, the high dose requirements for effective depression. This is detrimental as CMC destabilizes the froth at high dosages. Locust bean gum (LBG) brings attractive attributes like low charge density and insensitivity to pulp ionic strength. Therefore, this paper explored the feasibility of using alkaline gelatinized LBG as a CMC alternative depressant for pyroxene and talc. Bench flotation tests were conducted using Platreef ore to compare LBG and CMC's performance at 25 g/t, 50 g/t, and 100 g/t. This study showed that LBG and CMC yielded comparable pyroxene and talc depression (>80 %) at all dosages tested. Furthermore, at 100 g/t, the respective Pt recoveries of 88 % and 83 % illustrated that LBG was more effective than CMC at allowing Pt to float unhindered. Additionally, zeta potential measurements were conducted in the presence and absence of the depressant to establish the adsorption mechanisms. The zeta potential results showed that CMC and LBG adsorption onto pyroxene and talc surfaces were different due to their structural and ionic strength differences.